Negotiating new professional roles in retail’s workplace learning. Applying the negotiative theory of roles to a VET context - Raemy, Patric [Verfasser]; Barabasch, Antje [Verfasser] (My University, 2024)
„This study understands workplace learning as a social phenomenon and explores ways of how to successfully respond to industrial transformation out of a role-related perspective. The focus is on interactions of social actors in the process of structural change and economic adaptation. The goal of this inductive case study is to explore how 26 actors involved in workplace learning of one of the largest Swiss retailers, perceive, negotiate, and enact their social (and professional) roles vis a vis their company’s and industry’s new expectations. The narrations revealed several role-related themes in research about teaching and learning in VET. The study applies the process of role negotiation to a VET context by focusing attention on various aspects that emerged from the narratives as well as from theories of different academic fields and argues that role negotiation in the context of workplace learning might be in large parts moderated and supported by a company’s learning culture.“ (authors‘ abstract; BIBB-Doku)
Keywords: G 1.2.4.2.1 Handel, Instandhaltung, Reparatur von Kfz und Gebrauchsgütern; 370; Einzelhandel; Erwerbstätiger; Lernen am Arbeitsplatz; Rollenerwartung; Rollenverhalten; Soziale Rolle; Lernkultur; Fallstudie; Schweiz